2012
DOI: 10.1186/1744-8069-8-29
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Patch (5%) is No More Potent than Placebo in Treating Chronic Back Pain When Tested in a Randomised Double Blind Placebo Controlled Brain Imaging Study

Abstract: BackgroundThe 5% Lidocaine patch is used for treating chronic neuropathic pain conditions such as chronic back pain (CBP), diabetic neuropathy and complex regional pain syndrome, but is effective in a variable proportion of patients. Our lab has reported that this treatment reduces CBP intensity and associated brain activations when tested in an open labelled preliminary study. Notably, effectiveness of the 5% Lidocaine patch has not been tested against placebo for treating CBP. In this study, effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 45 publications
2
48
4
Order By: Relevance
“…A thorough examination of the data corroborated by several reports in the literature [13,24,28,29,35,49] demonstrated that 5% lidocaine relieves pain through a placebo effect. We also confirmed that the overall decrease in clinical pain was due to the use of the patch or treatment, and not a consequence of spontaneous remission in chronic pain because an untreated CBP group (observation only control) showed minimal change in back pain.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…A thorough examination of the data corroborated by several reports in the literature [13,24,28,29,35,49] demonstrated that 5% lidocaine relieves pain through a placebo effect. We also confirmed that the overall decrease in clinical pain was due to the use of the patch or treatment, and not a consequence of spontaneous remission in chronic pain because an untreated CBP group (observation only control) showed minimal change in back pain.…”
Section: Introductionsupporting
confidence: 61%
“…The present study is a reanalysis of data presented regarding the effects of 5% lidocaine on spontaneous pain of CBP [24]. In the latter study we showed that active treatment was not different from the placebo arm.…”
Section: Methodsmentioning
confidence: 55%
See 2 more Smart Citations
“…A study by Hashmi et al randomized 30 patients to either a 5% lidocaine patch or placebo patch 48 . After 2 weeks of use, both lidocaine and placebo patch groups reported a greater than 50% decrease in pain, suggesting that there may be no independent efficacy of 5% lidocaine patch for CLBP, but there is also a large and significant placebo effect, and that 5% lidocaine patch is not statistically significantly superior to placebo.…”
Section: Findings From Studies Grouped By Chronic Pain Syndromementioning
confidence: 99%